The Need for a National Land Use Act in the Philippines - Adoracion M. Navarro (Philippine Institute for Development Studies (PIDS), 2023)
Land use misgovernance in the Philippines arise due to the non-institutionalization of a national level framework for land use and the lack of harmonization of sector-specific laws on land resources. But the effort to push for a National Land Use Act (NaLUA) is almost three decades old already and advocates are finding it hard to hurdle the legislative mill. This study establishes that, to strengthen the push to enact a NaLUA, advocates need to employ a transdisciplinary approach and deepen through updated data and evidences the appreciation by policymakers and stakeholders of the arguments for having this legislation. The review of the theoretical foundations for land use analysis explains the evolution of land use analysis and the principles for land use governance. It also implies that a transdisciplinary approach is needed in advocating for a NaLUA. The assessment of data and evidences on conflicting land uses, land use misgovernance, and inadequacies of existing mechanisms for dealing with land use problems bolster the case for having a NaLUA. Insights of stakeholders during focus group discussions and key informant interviews confirm the findings from the assessment of data. Thus, the study concludes that enacting a NaLUA and ensuring that it is implemented through an appropriate institutional mechanism can help resolve land use conflicts in the country. In addition, it can support greater and sustainable value addition in the economy through land use optimization.
Keywords: 330; land use; land use analysis; land use changes; land use conflicts; land use planning; land use governance; National Land Use Act